Rattus elvira - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
373. Elvira Rat Cremnomys elvira French: Rat de Salem / German: Tamil-Nadu-Indienfelsratte / Spanish: Rata de Elvira Other common names: Elvira Cremnomys, Large Rock Rat Taxonomy. Rattus (Cremnomys) elvira Ellerman, 1946, Kurumbapatti, Salem District, Tamil Nadu, Eastern Ghats, India. This species is monotypic. Distribution. Known only from the type locality in Eastern Ghats, S India. Descriptive notes. Head-body 126-149 mm, tail 180-196 mm, ear 21-22 mm, hindfoot 30-32 mm. No specific data are available for body weight. Softfurred rat with a tail longer (c.130%) than head-body length. Tail is slightly bicolored. Dorsal pelage is brown gray, ventral white gray. Compared to the Cutch Rat (C. cutchicus), the Elvira Rat has a longer hindfoot and a larger skull. Females bear three pairs of mammae. Karyotype is 2n = 36. Habitat. Tropical dry deciduous scrub forest, where it isseen in rocky areas In arecent survey, populations of the Elvira Rat were found in rocky habitat, living in cliffs and the gaps between rocks, which were surrounded by sparse grass, herbs, and tall trees. Food and Feeding. No information. Breeding. No information. Activity patterns. Elvira Rats are terrestrial and probably nocturnal. Movements, Home range and Social organization. No information. Status and Conservation. Classified as Critically Endangered on The IUCN Red List because its area of occupancy is probably less than 10 km?, its extent of occurrenceis less than 100 km?2, all individuals are in a single location, and there is continuing decline in the extent and quality ofits habitat. Bibliography. Agrawal (2000), Molur et al. (2005). Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 737, DOI: 10.5281/zenodo.6887260